Microglia-Specific Promoter Activities of HEXB Gene - Shah, Sahil; Wong, Lilly M.; Ellis, Kendra; Bodnar, Brittany; Saribas, Sami; Ting, Julia; Wei, Zhengyu; Tang, Yuyang; Wang, Xianwei; Wang, Hong; Ling, Binhua; Margolis, David M.; et al. (Frontiers in Cellular Neuroscience, 2022)
Adeno-associated virus (AAV)-mediated genetic targeting of microglia remains a challenge. Overcoming this hurdle is essential for gene editing in the central nervous system (CNS). Here, we characterized the minimal/native promoter of the HEXB gene, which is known to be specifically and stably expressed in the microglia during homeostatic and pathological conditions. Dual reporter and serial deletion assays identified the critical role of the natural 5’ untranslated region (-97 bp related to the first ATG) in driving transcriptional activity of the mouse Hexb gene. The native promoter region of mouse, human and monkey HEXB are located at -135, -134 and -170 bp to the first ATG, respectively. These promoters were highly active and specific in microglia with strong cross-species transcriptional activities, but did not exhibit activity in primary astrocytes. In addition, we identified a 135 bp promoter of CD68 gene that was highly active in microglia but not in astrocytes. Considering that HEXB is specifically expressed in microglia, these data suggest that the newly characterized microglia-specific HEXB minimal/native promoter can be an ideal candidate for microglia-targeting AAV gene therapy in the CNS.